William Penn Chandler papers - Chandler, William Penn, 1820-
Letterbook (containing circa 130 letters) and 3 volumes of a diary detailing Chandler's business and social affairs while he was American consul to the city and kingdom of Tunis. Includes references to the gift of the Bey of Tunis of two camels to the U.S. Army Transport Service and the work of David Dixon Porter and Henry C. Wayne to convey them safely to the U.S. Correspondents include Ahmed and Mohammed, Beys of Tunis, Sir Edward Barnes, Charles H. Bell, Count Raffo (foreign minister of Tunis), and William Winthrop (consul at Malta).
Lawyer, editor and diplomat.
Collection material in English.
Keywords: Diplomatic and consular service, American -- Tunisia; United States. -- Army Transport Service; Camels; Porter, David D. -- 1813-1891.; Wayne, Henry C. -- 1815-1883.; Bell, Charles Henry, -- 1823-1893.; Ahmed, -- Bey of Tunis; Mohammed, Bey of Tunis; Barnes, Edward, -- Sir, -- 1776-1838.; Raffo, Count; Winthrop, William; Diplomats; Editors; Lawyers